2013
DOI: 10.1370/afm.1505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Facilitated Team Meetings and Learning Collaboratives on Colorectal Cancer Screening Rates in Primary Care Practices: A Cluster Randomized Trial

Abstract: PURPOSE The purpose of this study was to evaluate a primary care practicebased quality improvement (QI) intervention aimed at improving colorectal cancer screening rates. METHODSThe Supporting Colorectal Cancer Outcomes through Participatory Enhancements (SCOPE) study was a cluster randomized trial of New Jersey primary care practices. On-site facilitation and learning collaboratives were used to engage multiple stakeholders throughout the change process to identify and implement strategies to enhance colorect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 52 publications
1
59
0
Order By: Relevance
“…In contrast to the Supporting Colorectal Cancer Outcomes through Participatory Enhancements trial, 33 which showed no significant improvement in colorectal cancer screening after an intervention that combined learning collaboratives and on-site facilitation, in this population-based study we found an improvement in screening comparable to that with other interventions, such as audit and feedback, noted in the Colorectal Cancer Screening in Primary Care Practice study 34 and Building on Existing Tools to Improve Chronic Disease Prevention and Screening in Family Practice study. 35 Our results also contrast with those of our chart audit, which failed to show a significant difference in screening rates in a small subsample of patients.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the Supporting Colorectal Cancer Outcomes through Participatory Enhancements trial, 33 which showed no significant improvement in colorectal cancer screening after an intervention that combined learning collaboratives and on-site facilitation, in this population-based study we found an improvement in screening comparable to that with other interventions, such as audit and feedback, noted in the Colorectal Cancer Screening in Primary Care Practice study 34 and Building on Existing Tools to Improve Chronic Disease Prevention and Screening in Family Practice study. 35 Our results also contrast with those of our chart audit, which failed to show a significant difference in screening rates in a small subsample of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Field notes followed the method of Shaw and colleagues. 15 Immediately after each session, team members synthesized field notes into summaries that were coded and organized with the use of NVivo 10. Questionnaire data were collected after the 6-month intervention and at 12 months.…”
Section: Data Collectionmentioning
confidence: 99%
“…60 It would be pertinent to analyze the behavior within each group to understand such changes, as was done in a recent cluster study. 61 We integrated characteristics of the general practitioners into our analysis, and are further evaluating patients' behavior according to these characteristics and the practitioners' practices. This analysis of behavior of each cluster in a clustered response test is one of the challenges of research in primary care.…”
Section: Strengths and Limitationsmentioning
confidence: 99%